2013
DOI: 10.1073/pnas.1218424110
|View full text |Cite
|
Sign up to set email alerts
|

Large α-synuclein oligomers inhibit neuronal SNARE-mediated vesicle docking

Abstract: Parkinson disease and dementia with Lewy bodies are featured with the formation of Lewy bodies composed mostly of α-synuclein (α-Syn) in the brain. Although evidence indicates that the large oligomeric or protofibril forms of α-Syn are neurotoxic agents, the detailed mechanisms of the toxic functions of the oligomers remain unclear. Here, we show that large α-Syn oligomers efficiently inhibit neuronal SNARE-mediated vesicle lipid mixing. Large α-Syn oligomers preferentially bind to the N-terminal domain of a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
245
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(258 citation statements)
references
References 55 publications
(82 reference statements)
10
245
1
2
Order By: Relevance
“…Each fraction was subjected to a panel of commercially available antibodies detecting human αSyn (LB509, 4B12), mouse/human αSyn (4D6), phosphorylated and misfolded αSyn (pS129-αSyn and Syn514), and to a panel of antibodies generated to detect oligomeric and aggregated amyloid proteins (A11, OC, Officer), including o-αSyn (Syn33, F8H7) (23). We also included analyses with the 6E10 antibody detecting Aβ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] to determine whether the putative o-αSyn might be coupled to Aβ as a hybrid oligomer (24). Although a clear signal was detected in fraction 38, likely because of soluble APP or Aβ protofibrils, the pattern obtained with 6E10 was distinct from those found with αSyn antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each fraction was subjected to a panel of commercially available antibodies detecting human αSyn (LB509, 4B12), mouse/human αSyn (4D6), phosphorylated and misfolded αSyn (pS129-αSyn and Syn514), and to a panel of antibodies generated to detect oligomeric and aggregated amyloid proteins (A11, OC, Officer), including o-αSyn (Syn33, F8H7) (23). We also included analyses with the 6E10 antibody detecting Aβ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] to determine whether the putative o-αSyn might be coupled to Aβ as a hybrid oligomer (24). Although a clear signal was detected in fraction 38, likely because of soluble APP or Aβ protofibrils, the pattern obtained with 6E10 was distinct from those found with αSyn antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of h-αSyn WT is associated with a selective reduction in synapsins and complexins in mice (8). Given that large o-αSyn species were recently proposed to inhibit the docking of synaptic vesicles (9) and that synapsins regulate synaptic transmission and plasticity, we hypothesized that the increase in o-αSyn measured in our AD cohort could be related to the decrease in synapsins reported earlier (18). Measuring synapsin protein expression by Western blotting (8,18), we found that the abundance of o-αSyn measured by ELISA using LB509 as the detection antibody inversely correlated with total levels of synapsin isoforms (Ia/b and IIa/b) in the ITG (R 2 = −0.346, P = 0.0241) (Fig.…”
Section: Brain Levels Of Soluble αSyn Oligomers Correlate With a Selementioning
confidence: 99%
See 1 more Smart Citation
“…What can we learn from in vitro experiments studying the effect of a-synuclein on vesicle fusion? In assays reconstituting fluorescently labeled lipid vesicles with syntaxin and SNAP-25 in one case, and with VAMP2 in the other, a-synuclein was clearly shown to inhibit vesicle fusion in a concentration-dependent manner [18][19][20]. However, two of these studies argue that no direct binding of a-synuclein to the SNARE complex is needed for this inhibition[ 4 5 3 _ T D $ D I F F ] , and that inhibition is merely due to the lipid interaction of a-synuclein [19,21].…”
Section: Glossarymentioning
confidence: 99%
“…However, two of these studies argue that no direct binding of a-synuclein to the SNARE complex is needed for this inhibition[ 4 5 3 _ T D $ D I F F ] , and that inhibition is merely due to the lipid interaction of a-synuclein [19,21]. On the other side, for a-synuclein oligomers, binding to VAMP2 was found to be a crucial step for inhibiting vesicle fusion [20]. Together, these data draw again a controversial picture of a-synuclein function in SNARE-complex formation, but, at least for a-synuclein monomer, a mechanism that relies on membrane curvature stabilization, thus preventing premature fusion, seems likely.…”
Section: Glossarymentioning
confidence: 99%